Visualising antigen-specific T-cells during primary and persistent infection with Epstein-Barr virus - Tan, L; Tan, Linda Cheng-Choo (1999)
﻿ Cytotoxic T lymphocytes play an important role in mediating host immune reactions to viruses and other pathogens. Selective mechanisms operate during V(D)J recombination to enhance the diversity of the T cell repertoire that is generated, particularly in the CDR3 regions of the TCR, which mediate peptide recognition. The influence of V gene 3' sequences on the composition of the CDR3 loop in TCR β chains is analysed; in particular, A/T-rich coding termini are shown to be more susceptible to exonuclease "nibbling" during recombination. The recent development of peptide-MHC tetrameric complexes has enabled us to detect T lymphocytes according to their antigen specificity. Their use in detection and characterisation of EBV-specific CD8+ T cells during the primary acute phase of infection is described here. In particular, CTL responses to EBV lytic cycle antigens have only recently been reported and this study reveals unexpectedly high frequencies of activated, circulating CD8+ T lymphocytes which are directed towards lytic cycle epitopes, compared to well-characterised latent cycle antigens. In a second cohort of healthy long term asymptomatic donors, the frequency of CD8+ T cells recognising EBV lytic and latent cycle antigens was analysed by tetramer staining, ELISpot assays and limiting dilution assays; the tetramers detected antigen-specific CD8+ T lymphocytes with greater efficiency than other methods. Lytic cycle antigen-specific T lymphocytes were clearly detectable in all the asymptomatic donors, at higher frequencies than those specific for latent antigens. The final section of this thesis investigates the existence of enriched populations of EBV-specific T lymphocytes found within synovial joint fluid of rheumatoid arthritis patients. Although these cells do not appear to be directly involved in the initiation of disease, their ability to secrete proinflammatory cytokines within joints probably contributes to the maintenance of chronic inflammation in these patients.